Mechanism of Bitcoin and Investigation of the Studies in the Literature Related to Bitcoin - Kadiroglu, Zehra; Akilotu, Beyza Nur; Sengur, Abdulkadir (Institute of Electrical and Electronics Engineers Inc., 2019)
Bitcoin is a digital currency that uses cryptographic rules to regulation and generation units of currencies. In 2009, it was introduced by a person (or a group of people) using the name Satoshi Nakamoto before putting on the market as open source software. Bitcoin is a new payment system and investment tool for the purchase, storage and use of money as digitally. However, when people want to invest in bitcoin, the biggest factor they have to consider is how the price will change in the future. Recent developments in the field of machine learning have shown that some algorithms can provide appropriate solutions to predict future prices of crypto currencies. In this study, a detailed literature review is made about the studies using machine learning methods to estimate the future price of bitcoin. Basic and current information about bitcoin was included in this study. In addition, the theory of machine learning methods used is explained. The findings of the literature review show that machine learning methods can be successful in predicting bitcoin price. © 2019 IEEE.
Bitcoin Mekanizmasi ve Bitcoin'le Alakali Literatürde Yapilan Çalismalarin Incelenmesi
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: bitcoin; crypto currency; machine learning; price prediction